Kai-Wait sebagai Modal Sosial Inklusif: Tradisi Lokal dalam Membangun Solidaritas Lintas Agama di Maluku: Kai-Wait as Inclusive Social Capital: Local Tradition in Building Interfaith Solidarity in Maluku - Nathalia Debby Makaruku; Feky Manuputty; Simona Christina Henderika Litaay; Afdhal Afdhal (ITScience (Information Technology and Science), 2024)
This study aims to explore the concept of Kai-Wait as social capital in strengthening interfaith solidarity in the Maluku indigenous community, especially in Petuanan Leisela, Buru Island. Kai-Wait, a kinship system that integrates indigenous and immigrant residents, functions as a social mechanism that fosters trust, respect, and cooperation amidst religious diversity. With a qualitative approach through ethnographic studies, this study was conducted through participatory observation and in-depth interviews with indigenous leaders and members of the Buru indigenous community. The results of the study revealed that Kai-Wait not only strengthens social networks and customary norms, but also functions as a symbol of inclusive solidarity, able to embrace differences in religious and cultural identities. This tradition instills moral values ?? such as mutual respect, cooperation, and shared responsibility, which are continuously passed down to the younger generation. In addition, Kai-Wait shows its relevance as a local wisdom strategy in facing modern challenges, such as social polarization and identity conflicts, as well as being a bridge for social reconciliation. The novelty of this study lies in the identification of Kai-Wait as a form of pluralistic and inclusive social capital, different from other traditions in Maluku, such as Pela-Gandong, which tend to be limited to communities bound by customary oaths. This finding provides a significant contribution to the study of local wisdom, interfaith social solidarity, and social reconciliation. This study recommends the preservation of Kai-Wait values through formal and non-formal education, as well as the adaptation of this tradition to promote social harmony in diverse communities.